Impact of ethanol treatment on the technological characteristics, nutritional composition, and bioactivity of gluten-free breads produced with different microalgae - Sousa, Inês Gonçalves (2022)
Mestrado em Engenharia Alimentar / Instituto Superior de Agronomia. Universidade de Lisboa